2019
DOI: 10.1186/s12887-019-1454-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant body composition methods for obese pediatric patients

Abstract: BackgroundThere is no gold standard in body composition measurement in pediatric patients with obesity. Therefore, the aim of this study was to investigate if there are any differences between two bioelectrical impedance analysis techniques performed in children and adolescents with obesity.MethodsData were collected at the Department of Pediatrics and Adolescent Medicine in Vienna from September 2015 to May 2017. Body composition measurement was performed with TANITA scale and BIA-BIACORPUS.ResultsIn total, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
6
18
0
Order By: Relevance
“…In line with a previous study [15], our current assessment, using a much larger sample size (N=123 as compared to 38), con rmed that body composition determination in young obese patients yields signi cantly different results depending on whether it is conducted using the TANITA or the BIA device. Thus, TANITA-based determination of body composition overestimated BFP and FFM relative to BIA, and signi cantly underestimated FFM.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In line with a previous study [15], our current assessment, using a much larger sample size (N=123 as compared to 38), con rmed that body composition determination in young obese patients yields signi cantly different results depending on whether it is conducted using the TANITA or the BIA device. Thus, TANITA-based determination of body composition overestimated BFP and FFM relative to BIA, and signi cantly underestimated FFM.…”
Section: Discussionsupporting
confidence: 89%
“…We could also con rm previously indicated gender-related differences in body composition [15]. Independent from the bioelectrical impedance-based method, male patients had signi cantly lower BFP and signi cantly higher FFM, whereas FM did not differ between genders.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, it has been recognized that individuals with a similar BMI can vary considerably in their adiposity 53 . On the other hand, evidence indicated that the BIA device can overestimate BFP 54 . In the study by Tyrrell et al BIA-BFP overestimated DEXA-BFP by a mean of 2.53% 55 .…”
Section: Discussionmentioning
confidence: 99%